2022
DOI: 10.1186/s12884-022-04396-6
|View full text |Cite
|
Sign up to set email alerts
|

Mediolateral episiotomy and risk of obstetric anal sphincter injuries and adverse neonatal outcomes during operative vaginal delivery in nulliparous women: a propensity-score analysis

Abstract: Background The potential protective effect of mediolateral episiotomy for obstetrical anal sphincter injuries (OASIs) remains controversial during operative vaginal delivery because of the difficulties to take into account the risk factors and clinical conditions at delivery; in addition, little is known about the potential benefits of mediolateral episiotomy on neonatal outcomes. The objectives were to investigate the associations between mediolateral episiotomy and both OASIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…According to the researchers, this can be explained by a higher frequency of operative deliveries [ 40 ]. In turn, Desplanches et al (2022) found that mediolateral episiotomy reduces the risk of obstetric anal sphincter injuries among nulliparous women that are undergoing operative vaginal delivery [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the researchers, this can be explained by a higher frequency of operative deliveries [ 40 ]. In turn, Desplanches et al (2022) found that mediolateral episiotomy reduces the risk of obstetric anal sphincter injuries among nulliparous women that are undergoing operative vaginal delivery [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, episiotomy is employed to facilitate the birthing process, particularly in cases of fetal distress or when there is a need for operative vaginal deliveries, such as with forceps or vacuum assistance. The practice of episiotomy, widely adopted in the mid‐20th century, was initially perceived as a preventative measure against more severe spontaneous tears and subsequent pelvic floor disorders 3 . However, its routine use has been questioned in recent decades, leading to a more judicious and individualised approach.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of episiotomy, widely adopted in the mid‐20th century, was initially perceived as a preventative measure against more severe spontaneous tears and subsequent pelvic floor disorders. 3 However, its routine use has been questioned in recent decades, leading to a more judicious and individualised approach. Contemporary research emphasises the importance of evaluating maternal factors such as tissue elasticity, foetal size, and the progress of labour before deciding on an episiotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly reported indications for episiotomy include fetal distress, potentially complicated births (e.g., breech or shoulder dystocia), forceps or vacuum deliveries (in order to prevent obstetric anal sphincter injury), large babies, and preterm births [25][26][27][28]. However, these indications are based on tradition or clinical experience [29], with limited scientific evidence to support them [21,27], whereas the contribution of episiotomy to increased maternal morbidity is well established [20,26].…”
Section: Introductionmentioning
confidence: 99%